2015
DOI: 10.1016/j.vetmic.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and virological dynamics of a serotype O 2010 South East Asia lineage foot-and-mouth disease virus in sheep using natural and simulated natural inoculation and exposure systems

Abstract: Within-host infection dynamics of a recent field isolate of foot-and-mouth disease virus (FMDV), serotype O, topotype South East Asia, lineage Myamar'98 were evaluated in sheep using four different systems for virus exposure. Two novel, simulated natural, inoculation systems consisting of intra-nasopharyngeal (INP) deposition and aerosol inoculation were evaluated in comparison with two conventional systems: coronary band inoculation and direct contact exposure. All four exposure systems were efficient in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Clinical signs of FMD in sheep are often described as mild or inapparent [4]. However, some studies have reported severe clinical FMD in experimentally infected sheep characterized by fever, marked lameness, and vesiculo-erosive lesions on the feet and in the oral cavity [5,6]. Additionally, FMD outbreaks may lead to substantial lamb mortality, which is generally attributed to FMDV-associated myocarditis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical signs of FMD in sheep are often described as mild or inapparent [4]. However, some studies have reported severe clinical FMD in experimentally infected sheep characterized by fever, marked lameness, and vesiculo-erosive lesions on the feet and in the oral cavity [5,6]. Additionally, FMD outbreaks may lead to substantial lamb mortality, which is generally attributed to FMDV-associated myocarditis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The same study also highlighted the likely importance of the oropharyngeal tonsils during early infection in swine (Stenfeldt et al, 2014b). A comparative assessment of simulated natural virus inoculations systems for sheep showed that both aerosol challenge and intranasopharyngeal deposition were valid alternatives to the conventional methods of coronary band inoculation and direct contact exposure (Stenfeldt et al, 2015). In cattle, experiments where FMDV-A24 was administered either into the tongue epithelium or by aerosol supported data from experiments using O serotype viruses, confirming that initial replication occurs in the nasopharynx, followed by expansion in the lung and systemic viraemia.…”
Section: Literature Reviewmentioning
confidence: 89%
“…The same study also highlighted the likely importance of the oropharyngeal tonsils during early infection in swine (Stenfeldt et al., ). A comparative assessment of simulated natural virus inoculations systems for sheep showed that both aerosol challenge and intranasopharyngeal deposition were valid alternatives to the conventional methods of coronary band inoculation and direct contact exposure (Stenfeldt et al., ).…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Pigs are more effectively infected through oral exposure, with primary infection occurring within epithelial crypts of the oropharyngeal-and laryngopharyngeal tonsils [32,47]. Fewer efforts have been invested into detailed study of the early stages of FMDV infection of small ruminants, but current evidence suggests that primary infection in sheep occurs in either epithelial crypts of the oropharyngeal-or laryngopharyngeal tonsils (similar to pigs), or within the nasopharyngeal mucosa (similar to cattle) [25,29].…”
Section: Temporo-anatomical Progression Of Fmdv Infectionmentioning
confidence: 99%